Kesiapan Mahasiswa dalam Menyusun Tugas Akhir pada Program Studi Pendidikan Agama Islam dan Tadris Bahasa Inggris STAI Hubbulwathan Duri - Nova Yanti; Hisny Fajrussalam; Nurhalimah, Nurhalimah (Jurnal Pendidikan Islam Al-Affan, 2020)
The objectives of this study were to: 1) obtain information on how to describe students' readiness to face the munaqosah exam, and 2) to find out what factors affect the readiness to face the munaqosah exam. This research is a qualitative descriptive research. The data source selection technique, the researcher set a purposive sample. Purposive sampling is a method of sampling that is done by selecting subjects based on specific criteria set by the researcher. The criteria chosen were students who had already conducted proposal seminars from both the Islamic Religious Education and English Education study programs for the 2015 Academic Year. Participants or informants in this study were 33 people. Data collection techniques in this researcher through observation, interviews, and documentation. The results showed that the picture of student readiness to face the munaqosah exam was not ready to face it on time, namely 4 years or 8 semesters due to several factors, both in terms of internal factors and in terms of external factors. The factors that affect the readiness of students in facing the munaqosah exam include: 1) Internal factors, namely the lack of knowledge of students in writing theses because they are not guided from the beginning of writing, lack of understanding in compiling good and correct sentences into English, especially TBI study program students, There is a feeling of laziness in writing theses, reduced health conditions, there are students who experience trauma to ride their own motorbikes because they get and hear news of terrible collisions, 2) External factors, namely: there is no supervisor at the beginning of writing thesis, it is difficult for students to share time to write theses and guidance because of work, it is difficult for students to find reference books to support student research, there are final students who do not have personal laptops, there are students who have difficulty funding or costs Keywords: Readiness, Final Project, Study Program